'Having to learn this so late in our lives…' Swedish elderly patients' beliefs, experiences, attitudes and expectations of e-health in primary health care. (2nd January 2019) - Nymberg, Veronica Milos; Bolmsjö, Beata Borgström; Wolff, Moa; Calling, Susanna; Gerward, Sofia; Sandberg, Magnus
Abstract: Objective: The elderly are an increasing group and large consumers of care in Sweden. Development of mobile information technology shows promising results of interventions for prevention and treatment of chronic diseases. Exploring the elderly patients' beliefs, attitudes, experiences and expectations of e-health services helps us understand the factors that influence adherence to such tools in primary care. Material and methods: We conducted focus group interviews with 15 patients from three primary health care centers (PHCCs) in Southern Sweden. Data were analysed with thematic content analysis with codes and categories emerged from data during analysis. Results: We found one comprehensive theme: 'The elderly's ambivalence towards e-health: reluctant curiosity, a wish to join and need for information and learning support'. Eight categories emerged from the text during analysis: 'E-health – a solution for a non-existing problem?', 'The elderly's experiences of e-health', 'Lack of will, skills, self-trust or mistrust in the new technology', 'Organizational barriers', 'Wanting and needing to move forward', 'Concerns to be addressed for making e-health a good solution', 'Potential advantages with e-health versus ordinary health care' and 'Need for speed, access and correct comprehensive information'. Conclusions: Elderly patients in Sweden described feelings of ambivalence towards e-health, raising concerns as accessibility to health care, mistrust in poor IT systems or impaired abilities to cope with technology. They also expressed a wish and need to move forward albeit with reluctant curiosity. Successful implementation of e-health interventions should be tailored to target different attitudes and needs with a strong focus on information and support for the elderly. Key points: Exploring the elderly patients' beliefs, experiences, attitudes and expectations of the fast developing e-health services helps us understand the factors that influence adherence to such tools in primary care. Elderly patients in Sweden reported ambivalence and different experiences and attitudes towards e-health, raising concerns as accessibility to health care, costs and mistrust in poor IT systems or impaired abilities to cope with technology. They also expressed a wish and need to move forward albeit with reluctant curiosity. Successful implementation of e-health interventions should be tailored to target different attitudes and needs with a strong focus on information and support for the elderly.